2015
DOI: 10.1108/ijchm-01-2014-0020
|View full text |Cite
|
Sign up to set email alerts
|

Hotel cleanliness: will guests pay for enhanced disinfection?

Abstract: Purpose This study aims to propose that there may be a marketable segment of guests who are willing to pay a premium for guestrooms that are cleaned using enhanced disinfection techniques beyond the normal room cleaning procedures. Room cleanliness is important to hotel guests. Some hotel brands currently offer allergy-free rooms, charging a premium for this service. However, no hotel brands currently serve the market that is willing to pay more for enhanced disinfection. This exploratory study investigates wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 33 publications
1
78
0
6
Order By: Relevance
“…On the one end of the continuum, there are ‘optimistic hosts’ that will continue hosting on platforms whilst altering their practices to comply to the emerging need for better health and safety standards. These hosts seem to understand that health and safety are regarded as key in hospitality provision ( Zemke et al, 2015 ) and are willing to adapt their strategies, contrary to ‘indolent hosts’ who plan to continue their hosting activities without adaptation of their practices. The sentiments of ‘indolent hosts’ seem to emanate from their belief that their practices are adequately responsive to health standards or their decision to withstand the additional pressures of the platforms and guests on their practice (Buhalis et al, 2020; Farmaki et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one end of the continuum, there are ‘optimistic hosts’ that will continue hosting on platforms whilst altering their practices to comply to the emerging need for better health and safety standards. These hosts seem to understand that health and safety are regarded as key in hospitality provision ( Zemke et al, 2015 ) and are willing to adapt their strategies, contrary to ‘indolent hosts’ who plan to continue their hosting activities without adaptation of their practices. The sentiments of ‘indolent hosts’ seem to emanate from their belief that their practices are adequately responsive to health standards or their decision to withstand the additional pressures of the platforms and guests on their practice (Buhalis et al, 2020; Farmaki et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, to the best of our knowledge, this study is the first to examine the associated impacts of the Covid-19 pandemic on the increasingly popular P2P accommodation sector ( Farmaki and Kladou, 2020 ). Given that health, safety and cleanliness are considered key elements in hospitality decision-making ( Zemke et al, 2015 ), findings from this study will therefore shed light on the ongoing discourse on P2P hosts’ practices which have been argued to shift to more institutionalised hospitality services ( Farmaki and Kaniadakis, 2020 ). Third, the increase in infectious diseases across the world ( Jamal and Budke, 2020 ) will likely preoccupy hospitality practitioners in the foreseeable future.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Zemke, Neal, Shoemaker, and Kirsch (2015) emphasized on the importance of hotel room cleanliness towards guests' satisfaction and behavior. Breiter and Milman (2006) also indicated that cleanliness is most important for exhibition attendees.…”
Section: Authors (Year)mentioning
confidence: 99%
“…Given the growing consumer demand for hotel hygiene following the COVID-19 outbreak, enhanced cleanliness and sanitization to prevent or limit the spread of disease can be promoted as a selling point during and after this pandemic. Zemke et al (2015)…”
Section: Hygiene and Cleanlinessmentioning
confidence: 99%
“…Studies show that customers are influenced by hygiene and cleanliness conditions when making purchase decisions in a service environment (e.g., Choi, 2019;Hecht and Martin, 2006;Hoffman et al, 2003;Vilnai-Yavetz and Gilboa, 2010;Zemke et al, 2015). Hygiene and cleanliness issues have been considered in pandemic outbreaks as a culprit of disease (Alan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%